Genetic Variation in Essential Oil Constituents of Fennel (Foeniculum vulgare Mill) Germplasm. Issue 4 (18th May 2016) - Saxena, S.N.; Kakani, R.K.; Rathore, S.S.; Meena, R.S.; Vishal, M.K.; Sharma, L.K.; Agrawal, D.; John, S.; Panwar, A.; Singh, B.
Abstract: Ninety one fennel ( Foeniculum vulgare Mill.) germplasm lines collected from various geographical locations in India were evaluated for their essential oil content and its composition. Essential oil content ranged from 1.0 to 3.3%. Maximum lines had 2–3% essential oil. In all the germplasm lines eleven major compounds including α-pinene, camphene, β-pinene, myrcene, cymene, γ-terpinene, 4-allyl anisole/methyl chavicol or estragol, anethole, geranyl acetate and p-anisaldehyde were detected . Anethole was most abundant compound in all fennel germplasm lines which ranged from a minimum of 9.15% to a maximum of 96.64% with an average of 44.33%.Another predominant compound observed in essential oil of fennel germplasm lines was 4-allyl anisole/methyl chavicol or estragol, content of which ranged between 2.04 to 83.01%. A group of terpenoids consisting of α-pinene, camphene, β-pinene, myrcene, cymene and γ-terpinene accounted for 0.18 to 18.66% of essential oil of which γ-terpinene was contributed from a minimum of 0.13 % to a maximum of 14.95%. A significant negative correlation (r = -0.98) was observed between related compounds anethole with 4-ally anisole and γ-terpinene (r = -0.42). Further, the germplasm lines were grouped in different classes as per major essential oil constituents viz., anethol, γ-terpinene and 4-allyl anisole. Cluster analysis was done using ward's method based on the value of γ-terpinene, 4-ally anisole and anethole+estragol which resulted in to seven distinct groups of 91 germplasm lines.